EFL: The Effects of Being English Users On Bahasa Indonesia And Identity - Marcelinus Pascalis Nue (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
Since most Indonesians have familiarized themselves with English, their views of this language become a discussable issue. This study aimed to investigate Indonesians’ perspectives as English users. This study also examined the effects of English on their first language and identity. There were four participants with different social backgrounds selected in this study. They were intensively interviewed by using open-ended questions. By using a qualitative method, the data were classified into types of investment as the themes, such as identity, capitals and maneuvering ideology. This study found that the participants’ awareness of their investment has sent them to become contextualized English users. Then it would seem to indicate that English would not be the threat, even it could generate some benefits. Eventually, although this study was not within academic contexts, it revealed some pedagogical implications for the development of the language learning process in EFL classrooms.